Pseudophakic corneal edema caused by Descemet membrane detachment using high-resolution swept-source OCT imaging - Köppe, Maximilian K.; Khoramnia, Ramin; Auffarth, Gerd U.; Augustin, Victor A. (GMS Ophthalmology Cases)
Background: Small Descemet membrane detachments after cataract surgery are relatively common and most cases do not require any secondary surgical intervention and can be treated conservatively. However, in case of advanced Descemet membrane detachment (DMD), it needs to be recognized and treated appropriately. The advent of anterior segment imaging using optical coherence tomography (OCT) technology has made diagnosing pathologies of the anterior segment accurate and time efficient and has proven as an invaluable tool to guide decision making.Case presentation: A 71-year-old patient presented after complicated cataract surgery with decreased visual acuity and cloudy vision. On examination, best corrected visual acuity was 1.5 logMAR. A high-resolution swept-source OCT (Anterion, Heidelberg Engineering, Heidelberg, Germany) was used to better evaluate and visualize the extent of DMD. An anterior chamber gas bubble was injected to reattach the Descemet membrane (DM) to the corneal stroma. The success of the surgery was visualized using the high-resolution swept-source OCT. This revealed a completely attached Descemet membrane.Conclusions: Clinically, it can be difficult to distinguish the etiology of epithelial and stromal edema post cataract surgery. This case demonstrated the clinical usefulness using high resolution swept source imaging to guide clinical decision making in evaluating timing and treatment success of pneumodescemetopexy after complicated cataract surgery.